Upgrading German public services. The role of trade union campaigns and collective bargaining with regard to working conditions in day care centres, primary education and hospitals - Schulten, Thorsten; Seikel, Daniel (Düsseldorf, 2018)
"The development of the public sector in Germany during the last decade differs fundamentally from the experiences of many other European countries. In many respects Germany can be seen as forerunner of public sector reforms in Europe. Austerity-driven reforms of the public sector have been conducted long before the crisis, already starting in the 1990s. During this phase, public employment decreased and working conditions deteriorated. Privatizations led to a fragmentation of collective bargaining. However, the development of the German public sector changed direction in the second half of the 2000s. Since then, public sector employment increased and working conditions have been improved. This holds true, in particular, for public care services such as the three branches analysed in this study: day care centres, primary education and hospitals. As this study shows, trade unions played a major role in this process of upgrading public services."